PRIMARY LYMPH NODE PLASMACYTOMA – A RARE CLINICAL ENTITY - Sretenović, Snežana S (Srpski medicinski časopis Lekarske komore, 2024)
Introduction: Extramedullary plasmacytoma localized in the region of the head and neck represents less than 1% of tumors found in that region. Primary solitary localization of plasmacytoma in the lymph node, as the only manifestation of plasmacytoma, is rare, with less than 50 cases reported so far.Case report: A 58-year-old man came to the physician because of a painless swollen lymph node in the neck, afebrile, reporting no night sweats or weight loss. He was treated with broad-spectrum antibiotics for 10 days, but his health status did not change. A complete blood count (CBC) was performed, and normal test results were obtained.  The patient tested negative for biohumoral inflammatory syndrome. The ultrasound examination of the neck showed a lymph gland, 30 mm x 15 mm in size. The patient was referred to a maxillofacial surgeon; total lymph node extirpation was performed, and the excised node was sent for histopathological analysis. The following pathohistological finding was obtained: diffuse infiltration by plasmacytoid tumor cells stronlgly positive for: OCT2, BOB1, CD38, MUM1, lambda, CD31, VIM, and CD79 alpha; negative for kappa; positive for Ki67 in 30%. The conclusion of the pathohistological examination was lambda positive plasmacytoma. Bone biopsy showed the following: plasmocytes 4%. The findings of multi-slice computed tomography (MSCT) of the thorax, abdomen, and lesser pelvis were normal. Radiographic imaging of the skeleton also showed normal findings. The M protein, in both serum and urine, was negative. Virology tests showed that the patient was HBsAg positive, while he was HCV and HIV negative. Local radiation therapy was indicated along with active antiviral therapy.Conclusion: Each case of lymphadenopathy demands a serious and thorough approach to be established by the clinician. The question is whether an infection caused by the Hepatitis B virus may have served as a trigger for the development of plasmacytoma.
Keywords: plasmacytoma; lymph node; HBV infection